Morning vs. evening growth hormone injections and their impact on sleep-wake patterns and daytime alertness - Levshtein, Aglaya; Sharkia, Mohamad; Shimshi-Barash, Maya; Almagor, Tal; Albertsson-Wikland, Kerstin; Hochberg, Zeev; Pillar, Giora; German, Alina (Frontiers in Endocrinology, 2025)
ContextPhysiological growth hormone is secreted during slow-wave sleep. Traditionally, growth hormone (GH) therapy is given in daily GH injections before sleep. While morning and evening GH injections produce comparable effects on growth and IGF-1 levels, the evening schedule better imitates the physiological diurnal pattern of GH secretion and action. However, the inflexibility of bedtime injection schedules, coupled with the discomfort and psychological distress associated with the injection and local reaction, may cause sleep disturbances in patients, and may significantly burden them and their families.ObjectiveOur objective was to evaluate evening vs. morning daily GH injections with respect to sleep-wake pattern, duration, and activity index in children treated with growth hormone.DesignAn open-label, randomized crossover trial of 20 children (11 boys) 5–14 years of age with isolated growth hormone deficiency (n=12) and idiopathic short stature (n=8) treated with daily injections of median GH dose 33 (range13-46) mcg/kg/d was performed. Each subject received 2 weeks of evening injections and 2 weeks of morning injections. Patients' sleep-wake patterns and activity index were assessed by a 7-day actigraph covering the second week of each treatment schedule.ResultsAll subjects slept well, within recommended ranges for sleep parameters, regardless of whether they were receiving morning or evening GH injections. Results were comparable for all measures: total time in bed (min), 526.0 ± 51.8 vs 516.9 ± 57.4 for evening and morning GH injections, respectively; total sleep time (min), 512.4 ± 51.1 vs 504.3 ± 57.7; sleep efficiency (%), 93.6 ± 2.6 vs 94.2 ± 2.3; sleep onset latency (min), 8.9 ± 8.1 vs 7.4 ± 6.8; number of arousals per night, 14.5 ± 5.4 vs 12.5 ± 5.2; and 24-hour activity index, 68.3 ± 4.0 vs 67.0 ± 5.0, respectively. No difference was found between the growth hormone deficient and idiopathic short stature group. No difference was found between boys and girls.ConclusionsSleep-wake patterns and activity index were not affected by treatment schedules. We recommend that growth hormone injections take place at any regular time according to the family's convenience.